Finding the light : a mother's journey from trauma to healing - Henley, Marian (Andrews McMeel Publishing, 2024)
"This poignant graphic memoir describes the most difficult conversation between a mother and her son - the one about the two rapes she experienced as a young woman. It's something she always knew she would share with her son, but the process of doing so is harder - and more freeing - than she could have imagined" --